The Knowledge of Sustainable Waste Management Practices in Ilorin, Nigeria: Implication on Attainment of Sustainable Development Goals 3, 6, 11 and 13 (NTU Journal of Agriculture and Veterinary Science, 2023)
The current study has examined the knowledge of sustainable waste management practice in Ilorin, Nigeria. One hundred participants were randomly selected for this study. The data was analyzed using frequency count, percentage, mean and Pearson Product Moment Correlation (PPMC). The result showed that the average age of the respondents was 34.2 years. In addition, the study found that the participants' knowledg of the statement "Burning of waste materials pollute the air" was the highest ranked knowledge statement on sustainable waste management practices (x?= 2.57). Information on how to convert decompose waste into manure was the highest ranked information needs on sustainable waste management practices (x?= 2.45, P =0.001). There is a significant relationship between information needs and knowledge on sustainable waste management practices (r = 0.394,) at 1% level of significance. The study therefore has recommended that there should be a creation of public awareness on sustainable waste management practices and that every household should adhere to all the sanitation and environmental laws.